Influência da massa molar na biocompatibilidade de membranas de quitosana em tecido subcutâneo de ratos - Ribeiro, José Carlos Viana (2017)
Tissue engineering is based on the application of concepts from materials science and regenerative medicine with the aim of developing biomaterials capable of reconstructing or regenerating damaged tissue. In this context, chitosan (CS) has aroused a great deal of interest as one such biomaterial on account of its alleged properties of biocompatibility, bioactivity and the ease with which its chemical structure may be modified. CS is a naturally occurring polysaccharide obtained from chitin, an abundant and renewable source. It demonstrates great variability in terms of its main chemical characteristics, such as molar mass (MM) and the degree of deacetylation (DD), which may have an impact on its physical and biological properties. Numerous studies have investigated its use as a scaffold material in the regeneration of various types of tissue, including bone and periodontal tissues. However, few studies have related the possible influence of the MM of CS on its biocompatibility in vivo; this aspect still has not been clarified. The aim of the present study is to investigate the biocompatibility and bioactivity of CS membranes of different MM when implanted in the subcutaneous tissue of rats. CS membranes with a high molecular weight (HMW-CS) and low molecular weight (LMW-CS) were chemically characterized to determine their MM via gel permeation chromatography (GPC) and DD via potentiometric titration. Next, they were inserted into the subcutaneous conjunctive tissue in the backs of 24 animals and compared to a positive λ-carrageenan(Cg) control and a negative control. Biocompatibility was evaluated through histological analyses of the inflammatory leukocyte infiltrate, formation of granulation tissue and of fibrous conjunctive tissue, after 1, 7, 14 and 28 days. Bioactivity was investigated through immunohistochemical analyses carried out to identify the expression of the nuclear transcription factor NF-κΒ and the fibroblast growth factor FGF-2, which are proteins involved in the process of inflammation and tissue repair. The results showed that the chitosan membranes induced leukocyte infiltrate similar to the control after 7, 14 and 28 days, but lower than in the positive control. The LMW-CS induced a greater formation of granulation tissue and fibrous conjunctive tissue than HMW-CS, after 7 and 14 days, and than Cg after 7, 14 and 28 days, and showed inhibitory action on NF-κΒ at day 7. LMW-CS also showed a greater stimulatory effect than HMW-CS at day 1. The results suggest that LMW-CS induced a lower inflammatory response and promoted a faster regeneration of conjunctive tissue than HMW-CS, though both were found to be biocompatible. It may be concluded that MM influenced CS biocompatibility in vivo and this characteristic should be taken into consideration when developing and investigating CS-based scaffolds for tissue regeneration. The evaluated CS membranes presents a potential application for guided tissue regeneration.